Detection and characterization of polioviruses originating from urban sewage in Yaounde and Douala, Cameroon 2016–2017 - Daniel Kamga Njile; Serge Alain Sadeuh-Mba; Marie-Claire Endegue-Zanga; Marcellin Nimpa Mengouo; Marlise Dontsop Djoumetio; Franky Baonga Ba Pouth; Ousmane Madiagne Diop; Richard Njouom (BMC Research Notes, 2019)
Abstract Objective Transmission of wild polioviruses (WPVs) and vaccine-derived polioviruses (VDPVs) have been interrupted in Cameroon since July 2014. Subsequently, Cameroon withdrew Sabin type 2 from routine immunization in April 2016. This study aimed to investigate the detection rates and overtime distribution of the types of PVs recovered from urban sewage in Cameroon. Results From January 2016 to December 2017, 517 sewage specimens originating from Yaounde (325 specimens) and Douala (192 specimens) were analyzed. No WPVs and VDPVs were isolated in this study. In contrast, vaccine strains of poliovirus were detected throughout the study period. Isolates Sabin types 1 and 3 were sporadically detected whereas Sabin 2 was found only from January to May 2016 both in Yaounde and Douala. The absence of Sabin 2 in sewage specimens since June 2016 indicates its rapid disappearance after withdrawal from routine immunization in April 2016. This study provides substantial support to the observation that WPV and VDPVs have been successfully eliminated in Cameroon. However, it remains essential to maintain and extend high quality environmental surveillance as long as WPV reservoirs and VDPV outbreaks are detected in Africa.